Convergence in Local Press - (:unkn) unknown (IEEE, 2015)
Improvements in information and communication technologies have evolved the way of traditional broadcasting. This evolvement is currently being experienced in press, eliminating the specific and clear lines of every kind of medium. Changing news production/distribution process as well as readers' consumption tendencies have brought up some kind of negative presumptions related with the future of press. Taken into consideration on the level of widespread newspapers, this evolvement is siginificant in respect of the future of local newspapers which count around 1400 in Turkey, trying to survive financial reasons. Fullfilling the evolvement triggered by information and communication technologies successfully, local newspapers are now expected to fulfill their alternative journalism mission against global media contents with the help of new media environment.
Keywords: Local Press; New Media; Informatic Technology; Transformation; Convergence